Design and Demonstration of the Use of Automatic Hand Washing Sink Technology in Covid-19 Pandemic Conditions - Habib Satria; Mahliza Nasution; Moranain Mungkin; Yuan Anisa; Aristo Hardinata (Peneliti.net, 2022)
The design of automatic hand washing technology tools to support blended learning in the COVID-19 pandemic is very much on order. In designing and demonstrating a hand washing device, an automatic faucet modification is needed which consists of an IR sensor component (Proximity Infrared Switch Sensor) as an automatic on and off switch, then to support the faucet to work with a good system, a transistor that has been modified with a modified dynamo integrated into the system. connected to a mini pump. Then the other supporting components consist of a leg rack made of elbow iron, gallons of water, a sink, a water vacuum, an adapter and a dirty water disposal bucket. Then a demonstration of the tool was carried out to students at MTs Parmiyatu Wassa'adah. In demonstrating the tool there is a percentage of students with a positive response where as many as 14 students state very good with a percentage of 66.67%, and as many as 4 people state good with a presentation of 19% and as many as 3 people state quite well with a percentage of 14%. That is, the proportion of success from the design of this tool runs smoothly and can understand its functions and uses.